Порівняльний аналіз семантичних особливостей найменувань зірок у сучасних англійській, французькій та російській мовах - Когадєєва, Ганна Олександрівна; Kogadieyeva, A. O. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено дослідженню лексико-семантичних особливостей найменувань космічних об’єктів, а саме найменування зірок у різноструктурних мовах. Вперше здійснено спробу проаналізувати найменування зірок з погляду їх семантичних особливостей в англійській, французькій та російській мовах. Вступні зауваження містять інформацію про лінгвістичний статус космічних об’єктів, особливості номінації цих одиниць, а також екстралінгвістичні чинники, які мають вплив на виникнення і розвинення космонімів. Подано результати порівняльного аналізу семантичних особливостей найменувань зірок у трьох мовах. The article deals with the semantic features of names of space objects, namely the names of stars in the contrasted languages. The article presents an attempt to analyze names of stars from the view point of their semantics particularly in English, French and Russian languages, and to make their comparative analysis. The paper highlights the results of complex analysis of the nominating and lexico-semantic peculiarities of cosmonyms as well as the influence of extra-linguistic factors on the process of nominating the nonterrestrial objects. Introductory notes contain the information about the linguistic status of the space objects, providing different opinions on the problem concerning the place of cosmonyms in the onomastic field. The peculiarities of their nomination have been studied. The extra-linguistic factors, which influence the appearance and the development of cosmonyms have been revealed. Alongside, the results of comparative analysis of semanic features of the star names in modern English, French and Russian languages have been highlighted.
The Comparative Analysis of Semantic Features of the Star Names in the Modern English, French and Russian Languages
Keywords: космонімічна лексика; cosmonymic lexis; лексико-семантична група; lexico-semantic group; найменування зірок; star names